"Design of a Suspension Lever Mechanism in Biomedical Robotic System" - Voloshkin, A.; Tereshchenko, A.; Carbone, G.; Rybak, L.; Nozdracheva, A. (Frontiers in Robotics and AI, 2022)
The article discusses the design of a suspended lever mechanism with elastic elements, which is used as a safety device in a robotic system for the rehabilitation of the lower limbs. The article analyzes the existing mechanical structures of devices for rehabilitation, identifies the problems of operation, design, and safety systems and suggests a new design of the device. The process of reverse development of a lever mechanism scheme to ensure safety during rehabilitation of the lower limbs is presented. The design of the lever mechanism consists of movable levers connected by elastic elements. The device allows you to dampen the force during active rehabilitation. The power calculation of the lever mechanism in the rehabilitation system was carried out. The article addresses the issues present in the current mechanical designs with a brief discussion on the system architecture.